Mitigation of salt stress in rice plant at germination stage by using methyl jasmonate - Mahmud, Sakil; Sharmin, Shayla; Chowdhury, Bishan Lal Das; Hossain, Mohammad Anowar; Bhuiyan, Muhammad Javidul Haque (Asian Journal of Medical and Biological Research, 2016)
To explore the possibility of using methyl jasmonate (MeJA) for alleviation of salt stress, the present study was conducted where six rice varieties (BRRI dhan31, BRRI dhan46, Gota, Kajalsail, Pokkali and Pengek) were grown in non saline (0 dSm-1), saline (12 dSm-1), saline (12 dSm-1) + 10 ?M MeJA and saline (12 dSm-1) + 20 ?M MeJA conditions at germination stage (till the 9 days). MeJA was applied by imbibing seeds in it for 24 hours. To evaluate the effect of MeJA on saline stressed plant at germination stage, change in growth parameters namely germination percentage, shoot and root length, fresh and dry wt. of shoot, fresh and dry wt. of root and biochemical component- activity of alpha-amylase were monitored. Salinity had a minimum effect on final germination percentage (FGP) of rice varieties, but delayed in attaining it. MeJA had least positive effect. Salinity significantly reduced the shoot and root length, fresh and dry weight of all the varieties. MeJA had more decreasing effect in susceptible varieties while increasing effect in moderately tolerant and tolerant. Activity of alpha-amylase in germinated seed varied from 0.051 mg to 0.111 mg mal./mg tissue. At 12dSm-1 salinity, susceptible and moderately tolerant varieties showed significant reduction but tolerant showed significant increase. MeJA intensified the negative effect further in susceptible varieties. In tolerant and moderately tolerant varieties, increment in activity took place and 10 ?M had a better effect over 20 ?M MeJA. Asian J. Med. Biol. Res. March 2016, 2(1): 74-81